Growth performance and gut health of broilers fed heat- and enzyme-treated Vigna unguiculata and Cajanus cajan diets - Anjos, Filomena Dos; Dibner, Julia; Yan, Frances; Vazquez-Anon, Mercedes; Dierenfeld, Ellen. S.; Changule, Abilio P.; Garcia-Herreros, Manuel; Bila, Custódio G.; Chimonyo, Michael (Frontiers in Physiology, 2025)
IntroductionOptimizing broiler production performance while maintaining digestive health is a key challenge in poultry management. Dietary modifications, including the use of alternative protein sources and enzyme supplementation, can influence growth and gut health.MethodsThis study evaluated the effects of roasting, extrusion, and enzymatic supplementation of Vigna unguiculata (cowpeas) and Cajanus cajan (pigeon peas) on growth performance and gut health in broilers. A total of 210 one-day-old Ross male broilers were randomly allocated to seven dietary treatments (five replicates per treatment; six broilers per pen) in a completely randomized design. Experimental diets incorporated raw or heat-treated cowpeas or pigeon peas, with or without a mixed enzyme supplement (protease, xylanase, and phytase), replacing soybean meal at 400 g/kg inclusion.ResultsRoasting cowpeas or enzyme supplementation did not significantly affect body weight gain or cumulative performance index (p > 0.05). Roasting pigeon peas significantly improved chick performance (p < 0.05). Broilers fed diets containing raw cowpeas, raw cowpeas with enzymes, and both roasted and raw pigeon peas (with or without enzymes) exhibited reduced duodenal crypt depth compared to the control (p < 0.05). Furthermore, raw cowpeas, irrespective of enzyme supplementation, induced an immune response in the duodenum that was not observed in broilers fed the control diet, roasted cowpeas, or raw pigeon peas.DiscussionPartial substitution of maize and soybean meal with 400 g/kg roasted pigeon peas is a promising alternative in broiler nutrition, enhancing both performance and gut health. However, raw cowpeas may trigger an intestinal immune response, highlighting the importance of processing methods.